Right Of Cancellation For Booking Of Short - Term Accommodation Through Digital Economy Platform Before Movement Control Order (MCO) - Farhanin Abdullah Asuhaimi; Maheran Makhtar; Zuhairah Ariff Abd Ghadas (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
International Seminar on Syariah and Law (INSLA 2020) E-Proceedings “Hala Tuju Syariah Dan Undang - Undang Mendepani Pandemik Covid - 19” Organized by : Faculty of Syariah and Law, Universiti Sains Islam Malaysia 27-28 October 2020